Quanto espaço tem para o verde na selva de concreto? Eficiência das unidades de conservação na metrópole de fortaleza e vulnerabilidade da cobertura vegetal remanescente na malha urbana da cidade - Sampaio, Laymara Xavier (2023)
By 2070, around 85% of the global population will live in urban areas. In upper-middle income countries, such as Brazil, the number of cities will increase by 6% and the absolute population in these cities should continue to grow. This growth generates environmental risks, especially in the country with one of the highest levels of biodiversity on the planet. The municipality of Fortaleza is the fourth most populous municipality in the country, with the highest population density. This study aims to compute the total areas of remaining vegetation in the municipality of Fortaleza, to: calculate the total extent of areas that are within conservation units and the degree of degradation of vegetation cover in Conservation Units (CUs); measure the total remaining areas that are without legal protection by the National System of Conservation Units; identify fragments of native vegetation cover that are vulnerable to destruction. The analysis is based on geoprocessing techniques. The results show that Fortaleza has suffered significant deforestation, with only 16.29% of the area left covered by natural or semi-natural green areas. In total, Fortaleza has 12 terrestrial CUs. The majority are Sustainable Use Areas: five Environmental Protection Areas (EPA, 1886.09 hectares) and five Areas of Relevant Ecological Interest (AREI, 133.35 hectares). There are two Parks (State or Municipal Natural) with 1897.18 hectares of integral protection units within the municipality's boundaries. The level of effective protection of vegetation cover is between 70% and 75% in the Park and AREI categories but drops to less than 50% in the EPA. The CU in the best state of conservation is the Curió Forest AREI, with 81.7 hectares of vegetation cover conserved (effectively protected). At the other extreme, the CU with the worst conservation status is the Maranguapinho River EPA, with 91.5% of the terrestrial area degraded. We mapped 60 areas (2,923.16 hectares) with remaining preserved terrestrial ecosystems that are vulnerable to deforestation, as they are not protected by law. We have indicated these areas as priorities for conservation in Fortaleza. It is possible to build sustainable urban planning in Fortaleza, which preserves the remaining ecosystems already embedded in the urban matrix, in line with Sustainable Development Goal 11: "Make cities and human settlements inclusive, safe, resilient and sustainable"